2009
DOI: 10.1007/s00380-008-1127-9
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid is an independent predictor of arterial stiffness in hypertensive patients

Abstract: Increased arterial stiffness is an important marker for target organ damage in essential hypertension. Both serum uric acid (UA) and C-reactive protein (CRP) were reported to be associated with target organ damage. However, the influences of UA and CRP on large arterial stiffness were not well elucidated. This study included 200 essential hypertension patients (64 women) whose age was between 20 and 50 years old (mean age 41 +/- 8 years). None of the patients had diabetes mellitus or overt end-organ damage. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
3
34
0
3
Order By: Relevance
“…Furthermore, in multivariate logistic regression analysis, uric acid was an independent contributor to increased PWV in postmenopausal women even after adjusting for other cardiovascular risk factors including insulin resistance. Previous study has also reported that uric acid was associated with increased arterial stiffness in hypertensive patients [19]. The mechanism underlying the relationship of uric acid and arterial stiffness is not completely understood, but it was explained that endothelial dysfunction was associated with hyperuricemia [33].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, in multivariate logistic regression analysis, uric acid was an independent contributor to increased PWV in postmenopausal women even after adjusting for other cardiovascular risk factors including insulin resistance. Previous study has also reported that uric acid was associated with increased arterial stiffness in hypertensive patients [19]. The mechanism underlying the relationship of uric acid and arterial stiffness is not completely understood, but it was explained that endothelial dysfunction was associated with hyperuricemia [33].…”
Section: Discussionmentioning
confidence: 95%
“…There are few reports of the relationship between uric acid and PWV [13,18,19], and the results of these studies were inconsistent. Moreover, there is no information on the relationship between uric acid and PWV in postmenopausal women.…”
Section: Introductionmentioning
confidence: 90%
“…As renal function deteriorated in the hypertensive patients, arterial stiffness could be overestimated. 22 Autonomic tone, and sympathetic/parasympathetic activity may increase vascular tone and resistance. 23 Therefore, we considered resting heart rate as a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness can be measured at different arterial segments and sites, and by use of different techniques which include regional carotid-femoral pulse wave velocity (cfPWV), brachialankle PWV (baPWV), and local carotid and femoral stiffness. Several studies have assessed the association between uric acid and regional arterial stiffness, with conflicting results [11][12][13][14][15][16][17][18][19][20][21]. However, in most of these studies [12,14,[16][17][18][19][20], arterial stiffness was determined via the assessment of baPWV.…”
Section: Introductionmentioning
confidence: 98%